Elucidation of novel, alternative, fiber-reinforced iron-based pozzolanic composites as SCMs - Hafiz Muhammad Nadir; Ash Ahmed; Ikram Moshi (Academia Materials Science)
The researchers pioneered incorporating waste materials exhibiting pozzolanic properties and waste fibers from diverse industrial/agricultural fields into the construction industry to formulate enhanced, greener supplementary cementitious composites (SCMs). This research focused objectively on the formulation/evaluation of low-CO2-embodied greener construction materials known as “novel, alternative, fiber-reinforced iron-based binary/ternary pozzolanic composites (abbreviated as NAFRIC)”. The composites incorporated iron powder (Fe), metakaolin (MK), pulverized fly ash (PFA), ground granulated blastfurnace slag (GGBS), palm ash, silica fume, and limestone, which are anticipated to absorb CO2 while producing siderite (ferrous carbonate FeCO3). All the NAFRIC mixes formulated in this study demonstrated up to 4–13% improvement in compressive strength and 70–130% in flexural strength with an enhanced rupture modulus/post-crack ductility. The ternary pozzolanic iron-based fiber-reinforced concrete (FRC) composites containing 8% MK + 10% PFA + 10% GGBS and steel/polypropylene/polyethylene terephthalate (PET) fibers performed the best with attaining up to 70 MPa compressive and up to 8.9 MPa flexural strengths. The sulfate testing evaluated the durability of NAFRIC SCMs formulated in a 1:2:3 ratio better than cement concrete control mix with a 1:1:3 ratio. NAFRIC specimens demonstrated minimal surface deterioration/elongation and negligible/no strength reduction after 270 days of concentrated sulfate attack. The microstructural analysis using X-ray diffraction/fluorescence, scanning electron microscopy/energy-dispersive analysis with X-ray spectroscopy supported the strength and durability parameters by showing minimal/no ettringite formation and increased calcium silicate hydrates gel formation due to the use of FeCO3 and pozzolans. The study demonstrated the sustainable use of these better-performing NAFRIC SCMs with 10–12% reduced embodied CO2 as eco-friendly high-strength SCMs with enhanced engineering/environmental benefits.